Influência espaço-temporal e fisiológica na absorção de nutrientes e elementos tóxicos por Eichhornia crassipes visando o uso adequado da sua biomassa: o caso do Rio Apodi/Mossoró - RN - Martins, Daniel Freitas Freire (2009)
This study aims to determine the amount of nutrients and toxic elements in aquatic macrophytes of species Eichhornia crassipes present in River Apodi/Mossoró - RN and check some of the possibilities of using the biomass produced, based on the influence of space - temporal and physiological absorption of nutrients by plants. For this, was determined: Leaf area, Leaf wet mass, Leaf dry mass, Real humidity, Apparent humidity, Ash, Total nitrogen, Crude protein, Calcium, Magnesium, Potassium, Total phosphorus, Sodium, Iron, Copper, Manganese, Zinc, Nickel, Cobalt, Aluminum, Cadmium, Lead and Total chromium at different times, 2 sampling points and 2 parts of plants (leaves and roots). The results show that the levels of nutrients, protein and toxic elements present in plant tissue of Eichhornia crassipes are influenced by spatial, temporal and physiological variability. In general, because the maximum values in the dry matter for total nitrogen (4.4088 g/100g), crude protein (27.5549 g/100g), total phosphorus (0.642 g/100 g), calcium (1.444 g/100g), magnesium (0.732 g/100 g), potassium (7.51 g/100 g), copper (4.4279 mg/100g), manganese (322.668 mg/100g), sodium (1.39 g/100g), iron (194.169 mg/100g) and zinc (3.5836 mg/100g), there was the possibility of using biomass of Eichhornia crassipes for various purposes such as in food animal, products production for human consumption, organic fertilizers, fabrication of brick low cost, and crafts. For all these applications requires a control of the levels of substances in plant tissue. Based on the levels of nutrients and crude protein, the younger plants (0 Month) would be best to have their biomass used. Moreover, one factor that contributes to the use of larger plants (6 Months), the levels of toxic elements which have significantly small or below the detection limit. Therefore, further studies quantifying the biomass produced/m2 at 0 and 6 months are needed for a more correct choice for the best time of harvest